A summary of the main actions of the Iranian government during the Covid-19: From March 5 until December 20 in 2020 - Reyhaneh Sefidkar; sajjad Bahariniya; Farzan Madadizadeh (Shahid Sadoughi University of Medical Sciences, 2021)
Dear Editor in Chief During the disease epidemic in Iran, the government first considered emergency measures for the center of the disease epidemic, the Qom province, and after that by observing new cases in Tehran, Gilan, and Mazandaran provinces, which are the adjacent provinces to Qom province, the emergency measures for these three provinces were considered as well (1).